Hope and its relationship with treatment/ physical related factors in lung cancer patients receiving immunotherapy - Chih-Chien Hsu; Yun-Hsiang Lee; Min-Ru Chen; Chih-Hsin Yang; Jin-Yuan Shih; Wei-Yu Liao; Meng-Ping Hsiao; Yeur-Hur Lai (Journal of the Formosan Medical Association, 2025)
Backgroundpurpose: Immunotherapy is a new treatment option for patients with Lung Cancer (LC). However, relatively limited research has explored about patients’ perception of hope and its associated factors during the process. This study aimed to examine level of perceived hope and the factors related to hope, with a particular focus on treatment and physically related factors, in LC patients receiving immunotherapy. Methods: A cross-sectional study was conducted and patients who had already received at least one immunotherapy cycle were recruited from two hospitals in northern Taiwan. The questionnaire included a background information form, the Herth's Hope Index, and the Symptom Severity Scale. Stepwise regression was applied to identify the most robust factors related to level of hope in the participants. Results: A total of 130 patients were recruited. Overall, patients reported moderate to high levels of hope and mild symptoms. Fatigue, weakness, appearance changes, pruritus, and shortness of breath were identified as the most severe symptoms. Further regression analysis showed that patients with poor performance status, less immunotherapy cycles, higher level of fatigue, and more severe pruritus reported to have lower level of hope which explained 47% of the variances. Conclusion: This study revealed that lung cancer patients undergoing immunotherapy had moderate level of hope. Patients’ performance status, selected symptoms and times of receiving immunotherapy were the robust factors related to hope. Systematic assessment of patients' symptoms and the development of appropriate interventions to reduce distress and enhance hope are strongly recommended for both clinical care and research.